Implementasi Item-Based Collaborative Filtering Untuk Rekomendasi Film - Rayhan Rizal Mahendra; Fetty Tri Anggraeny; Henni Endah Wahanani (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
Item-based collaborative filtering is a popular technique in recommendation systems that aims to provide suggestions for films to watch or services to users based on similarities between items. In this approach, the similarity between items is calculated using metrics such as cosine similarity, allowing the prediction of user preferences for items that have never been rated. This research implements Item-based collaborative filtering using datasets from Kaggle. Experimental results show that the resulting model is able to provide recommendations with significant improvements in evaluation metrics such as Mean Absolute Error (MAE) and Root Mean Square Error (RMSE) of 3.05 and 3.26. This shows that the smaller the value, the better.